Evaluating Interactive Fatigue Management Workshops for Occupational Health Professionals in the United Kingdom - Sheila Ali (Safety and Health at Work, 2014)
Background: Disabling fatigue is common in the working age population. It is essential that occupational health (OH) professionals are up-to-date with the management of fatigue in order to reduce the impact of fatigue on workplace productivity. Our aim was to evaluate the impact of one-day workshops on OH professionals' knowledge of fatigue and chronic fatigue syndrome (CFS), and their confidence in diagnosing and managing these in a working population. Methods: Five interactive problem-based workshops were held in the United Kingdom. These workshops were developed and delivered by experts in the field. Questionnaires were self-administered immediately prior to, immediately after, and 4 months following each workshop. Questionnaires included measures of satisfaction, knowledge of fatigue and CFS, and confidence in diagnosing and managing fatigue. Open-ended questions were used to elicit feedback about the workshops. Results: General knowledge of fatigue increased significantly after training (with a 25% increase in the median score). Participants showed significantly higher levels of confidence in diagnosing and managing CFS (with a 62.5% increase in the median score), and high scores were maintained 4 months after the workshops. OH physicians scored higher on knowledge and confidence than nurses. Similarly, thematic analysis revealed that participants had increased knowledge and confidence after attending the workshops. Conclusion: Fatigue can lead to severe functional impairment with adverse workplace outcomes. One-day workshops can be effective in training OH professionals in how to diagnose and manage fatigue and CFS. Training may increase general knowledge of fatigue and confidence in fatigue management in an OH setting.